Fatty Acid Composition of Chironomidae Larvae in Different Seasons - Kara, Tuba; Tellioglu, Ayda; Aydin, Sevinc (Asian Journal of Chemistry, 2012)
In the present study, seasonal changes in the fatty acid composition of the chironomidae larvae were determined by gas chromatography. When the seasonal variation of fatty acids were compared, a significant increase were observed caproic acid (6:0), palmitic acid (16:0), palmitoleic acid (16:1 n7), stearic acid (18:0), oleic acid (18:1 n9), linoleic acid (18:2 n6) and arachidonic acid (20:4 n6) in all seasons. A significant increase were observed in myristic acid (14:0) in spring and winter; margaroleic acid (17:1) in autumn; eicosapentaenoic acid in spring and linolenic acid (18:3 n3) in spring, summer and winter. When the fatty acids were compared, caproic acid (6:0), palmitic acid (16:0), stearic acid (18:0) and linoleic acid (18:2 n6) level were found to be significantly high. When fatty acids were compared statistically, differences were detected between seasons (p < 0,001). In conclusion, it is suggested that the reason for these differences is due to the variety of food in different seasons and larval development feature.
Keywords: Chironomidae larvae; Fatty acids; Seasonal variation